Elements of Folk Pragmatics in Bosnian Proverbs - Bulić, Halid (Poznańskie Studia Slawistyczne, 2023)
This paper discusses the views on pragmatic subjects explicitly mentioned or implied in Bosnian folk proverbs. For the purposes of the research, three collections of proverbs were analyzed: Narodno blago by M. K. Ljubušak (1887), Na nebu paučina by V. Gunić (1999) and Krajiške izreke i poslovice by A. Sijamhodžić (2017). In these collections many proverbs that deal with pragmatic subjects are recorded. Such proverbs are cited and commented upon in the central part of the paper. They mostly refer to the effects of language use, language as a sign of personality or identity, appropriateness, indirectness, politeness, speech acts (primarily promises, advice and compliments) and co-operation (Grice’s Cooperative Principle, its maxims, and hedges).